Delayed evoked potentials in zebra finch (Taeniopygia guttata) under midazolam-butorphanol-isoflurane anesthesia - Yu,Pin Huan; Hsiao,Yi-Tse (PeerJ, 2019)
Avian animals are visually inclined, which has caused them to attract increasing attention for visual neurophysiology or electrophysiology studies, including the study of the visual evoked potential (VEP). VEP has developed into an investigative tool for understanding the physiology and the pathology of the visual pathway. Chemical restraint is a common method to minimize motion artifacts in animals when acquiring VEP data, but little is known about its influence on the signal in an avian animal. In addition, it is difficult to make comparisons between conscious state data when the animals are ultimately under anesthesia. Therefore, finding drugs and developing protocols that have an acceptable effect is valuable. We compared the local field potentials of physically and chemically restrained zebra finches (Taeniopygia guttata), a small avian species, to simulate a relatively challenging recording condition. Finches were sedated with midazolam-butorphanol, and anesthesia was maintained by isoflurane. Electrodes were implanted into the left nucleus rotundus, which is a visual nucleus in birds. The VEPs of the control group (N = 3) were recorded after they fully recovered and were restrained by towels. The other birds (N = 3) were recorded under anesthesia. The results show that without the visual stimuli, anesthesia generally suppressed the overall power of field potentials. However, by focusing on the spectra during VEPs, visual stimuli still triggered significant VEPs in frequencies below 30.8 Hz, which were even stronger than towel-restrained birds. The drugs also prolonged the latency of the VEP, increased the duration of the VEP when compared to towel-restrained birds. As regard to towel-restrained zebra finches, the field potentials were less synchronized and may need data preprocessing to have clear VEPs. In conclusion, the current study presents evidence of basic VEP for zebra finch under midazolam-butorphanol-isoflurane anesthesia with a protocol that is a safe and feasible anesthetic combination for chemical restraint, which is particularly useful for small animals when obtaining evoked potentials.
Keywords: Visual evoked potential; Zebra finch; Midazolam; Butorphanol; Isoflurane; Nucleus rotundus